Development Of Microcontroller Controlled Computer Numerical Control (Cnc) Router Machine With Graphical User Interface (Gui) - Yaziz, Mohd Farizul Hazimi Mohd (2016)

(untitled)
This research is about developing a microcontroller controlled Computer Numerical Control (CNC) router machine with Graphical User Interface (GUI). The microcontroller able to work as control software for machining operation monitoring by flashing Grbl - an open source, high performance G-code-parser and CNC milling controller to the microcontroller. The GUI's role as a mean of communication between computer and the microcontroller. The CNC router machine able to perform 3-D coordination using its three axes. For positioning and axes motion control,stepper motors are incorporated with stepping motor drivers and AVR microcontroller. The computer is used to create G-code programming which is a standard industry machining code. Other peripheral devices such as limit switches are integrated with AVR microcontroller for machine's zero reference point calibration as well to perform hard limit function. The first challenge is to build a working GUI for machine interface using Microsoft Visual Basic 2010 Express programming language and secondly is to interface all these components together with the AVR microcontroller. With the improvement implementation of the CNC router machine able to reduce fault error occurrence from 60% to 5%, the built GUI able to function 100% as intended to, and the accuracy of the CNC router machine with less than 1% error, the objective of this research is achieved. Improvements that can be done on the system are to further developing the Grbl system, the GUI and the hardware system to improve the performance of the CNC router machine.